Descriptions of three new species of the genus Symmorphus Wesmael, 1836 (Hymenoptera: Vespidae: Eumeninae) from South Korea, with an updated revised key to Far Eastern species - Kim, Jeong-Kyu (Zootaxa, 2017)
Three new species of the genus Symmorphus Wesmael, 1836 are described with materials from South Korea and Far eastern Russia: Symmorphus kurzenkoi Kim sp. nov., S. truncatoclypeus Kim sp. nov., S. yamanei Kim sp. nov. All are members of the subgenus Symmorphus Wesmael 1836. S. kurzenkoi Kim sp. nov. is likely to be closely related to Symmorphus fuscipes in having well developed and completely closed propodeal submedian carina, but is clearly different from the latter in the shape of metasomal tergum 1 that is not markedly narrowed toward base. Within the S. murarius group proposed by Cumming 1989, Symmorphus truncatoclypeus Kim sp. nov. is unique in having a clypeus with apical margin completely truncated. S. yamanei Kim sp. nov. is separated from congeners by following combination of characteristics: uniformly lengthened mesosomal setae; vestigial epicnemial carina; areolate mesepimeron; propodeal submedian carina that is somewhat strongly developed though doubled and not clearly closed dorsally; weakly raised basal transverse carina on metasomal tergum 1; faintly foveate-reticulate dorsomedian portion of metasomal tergum 1. Re-description of S. tsushimanus Yamane 1990, which is the most poorly known species in the Far East, is presented based on the holotype. Finally, an updated revised determination key to Far Eastern species, supplemented by digital images and line drawings, is given.